2017
DOI: 10.18632/oncotarget.14706
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR) mutations in non-small cell lung cancer (NSCLC) of Yunnan in southwestern China

Abstract: To investigate the Epidermal Growth Factor Receptor (EGFR) mutation status in non-small cell lung cancer (NSCLC) in Yunnan province in southwestern China, we detected EGFR mutation by Amplification Refractory Mutation System (ARMS) polymerase chain reaction (PCR) using DNA samples from 447 pathologically confirmed NSCLC specimens (175 tissue, 256 plasma and 16 cytologic samples). The relationship between EGFR mutations and demographic and clinical factors were further explored. Subgroup analyses according to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
5
25
0
Order By: Relevance
“…Next, in our clinical study, we observed a high clinical sensitivity (82.0%) and specificity (100%) of ADx-SuperARMS EGFR mutation blood testing. E19Dels and L858R were the two most common EGFR mutation subtypes in our study, just as reported in previous Chinese NSCLC studies[ 47 , 48 ]. Compared to the performance of ddPCR[ 30 ], ADx-SuperARMS provides a better sensitivity of E19Dels (88% vs. 82%) and L858R (89% vs. 80%) mutation detection in plasma with a specificity of 99% and 100% respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Next, in our clinical study, we observed a high clinical sensitivity (82.0%) and specificity (100%) of ADx-SuperARMS EGFR mutation blood testing. E19Dels and L858R were the two most common EGFR mutation subtypes in our study, just as reported in previous Chinese NSCLC studies[ 47 , 48 ]. Compared to the performance of ddPCR[ 30 ], ADx-SuperARMS provides a better sensitivity of E19Dels (88% vs. 82%) and L858R (89% vs. 80%) mutation detection in plasma with a specificity of 99% and 100% respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The patient cohort in the present study was primarily from Yunnan Province, an undeveloped, secluded and mountainous province of southwestern China, therefore a number of individuals in this region are unable to afford the relatively expensive cost of PET-CT and gene mutation detection, directly leading to the small sample size. Secondly, a bias could have existed in the process of the patient selection process since the majority of the patients resided in Yunnan Province that is known for high lung cancer rates (46)(47)(48). Thirdly, differences in metabolic parameters among different EGFR mutations, and between EGFR mutation and other important mutations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Xuanwei City, in the northeastern part of Yunnan province, China, is 6,257 km 2 and lies on high plateau punctuated by mountain ridges 3 . Its total population is approximately one million.…”
Section: Introductionmentioning
confidence: 99%